2013
DOI: 10.1177/1558689813508225
|View full text |Cite
|
Sign up to set email alerts
|

Mixed Methods in Emerging Academic Subdisciplines

Abstract: This article examines the prevalence and characteristics of mixed methods research in the relatively new subdiscipline of sport management. A mixed methods study is undertaken to evaluate the epistemological/philosophical, methodological, and technical levels of mixed methods design in sport management research. The results indicate that mixed methods research is still rarely used, poorly legitimized and often weakly designed in this field. Our conclusions lead to the hypotheses that the more central a researc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(22 citation statements)
references
References 35 publications
0
20
0
2
Order By: Relevance
“…Based on our experience and work, we can now confidently state that the “multifaceted” perspective (Tashakkori and Teddlie, 2010, p. 274) offered by a mixed methods research approach (Johnson et al, 2007) is now widely present in the field of sport and physical activity (van der Roest et al, 2015). An optimal approach would be to take a wide-angle perspective while resisting the temptation to pose an overly broad research question, with the ultimate aim of making future research more effective.…”
Section: Sport and Physical Activity As A New Substantive Area In MIXmentioning
confidence: 86%
“…Based on our experience and work, we can now confidently state that the “multifaceted” perspective (Tashakkori and Teddlie, 2010, p. 274) offered by a mixed methods research approach (Johnson et al, 2007) is now widely present in the field of sport and physical activity (van der Roest et al, 2015). An optimal approach would be to take a wide-angle perspective while resisting the temptation to pose an overly broad research question, with the ultimate aim of making future research more effective.…”
Section: Sport and Physical Activity As A New Substantive Area In MIXmentioning
confidence: 86%
“…This approach targets the established sports system and includes the expertise of non-profit sports clubs, which to some extent know the participants in their local community and know how to organize the activities. Vail (2007) demonstrates how top-down initiatives that ignore community needs have failed to succeed in sustaining sports participation. FF is a top-down concept, but, as we have shown, it makes room for local input and bottom-up activities and proves beneficial for the clubs, which encourages them to continue their work.…”
Section: Discussionmentioning
confidence: 99%
“…Data used to explore the concept of FF come from both qualitative and quantitative methods. This combination of methods will provide a fuller understanding and stronger conclusions to the research questions we would like to explore than would be the case with a monomethod approach (van der Roest et al, 2013). The DFA provided the contact information for the participants but had no influence on the choice of research participants.…”
Section: Study Design and Participantsmentioning
confidence: 99%
“…These authors reported 24% of articles presented mixed methods research across five elite education journals, but only 6% in psychology and sociology, indicating further examples of uneven distribution of methodology across specific fields of inquiry. A striking study by van der Roest, Spaaij, and van Bottenburg (2015) demonstrated the scarcity of mixed methods research in the field of sports management, identifying only 1.7% of publications as using this approach. Whilst SoTL is having an internal debate about research study design with concerns about plurality of approaches, our results demonstrate a fairly even spread of approaches when compared to other fields of inquiry.…”
Section: Discussionmentioning
confidence: 99%